2008
DOI: 10.1002/ijc.23834
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of 3p21.31 tumor suppressor genes in head and neck squamous cell carcinoma: Correlation with progression and prognosis

Abstract: The aim of our study was to analyze the alterations of some candidate tumor suppressor genes (TSGs) viz. LIMD1, LTF, CDC25A, SCOTIN, RASSF1A and CACNA2D2 located in the chromosomal region 3p21.31 associated with the development of early dysplastic lesions of head and neck. In analysis of 72 dysplastic lesions and 116 squamous cell carcinoma of head and neck, both deletion and promoter methylation have been seen in these genes except for CDC25A and SCOTIN where no methylation has been detected. The alteration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 46 publications
9
57
1
Order By: Relevance
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and includes tumors of the pharynx, oral cavity and larynx [1][2][3][4]. Curcumin (diferuloylmethane), a principle ingredient in the spice turmeric, is well known for its anti-carcinogenic, antiinflammatory and pharmacological properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide and includes tumors of the pharynx, oral cavity and larynx [1][2][3][4]. Curcumin (diferuloylmethane), a principle ingredient in the spice turmeric, is well known for its anti-carcinogenic, antiinflammatory and pharmacological properties [5].…”
Section: Introductionmentioning
confidence: 99%
“…Various classes of tumors demonstrate a loss of RASSF1A protein. A subset of tumors was identified that exhibits substantial RASSF1A protein expression and shows increased tumor progression, such as renal cell carcinoma [4], head and neck squamous cell carcinoma [5], ductal carcinoma in situ [6], endometrial carcinoma [7], esophageal and nasopharyngeal carcinoma [8], gastric carcinoma [9], etc. However, to date, no studies have investigated the association between RASSF1A protein expression and clinicopathological features of HCC among a large patient number by immunostaining.…”
Section: Introductionmentioning
confidence: 99%
“…The different HPV types are characterized by variations in the DNA sequences of L1 and divided into high-and low-risk types [15]. High-risk types include HPV- 16,18,31,32,33,35,39,45,51,52,56,58,59,66, and 68, and low-risk types are HPV-6, 11, 42, 43, and 44. The high-risk HPV (HR-HPV) types 16 and 18 are the most common etiological agents in 70% of cervical cancers globally.…”
Section: Hpv Biologymentioning
confidence: 99%